Personality Traits and Impulsivity Tasks Among Substance Use Disorder Patients: Their Relations and Links With Retention in Treatment - Gómez-Bujedo, Jesús; Lozano, Óscar M.; Pérez-Moreno, Pedro Juan; Lorca-Marín, José Andrés; Fernández-Calderón, Fermín; Diaz-Batanero, Carmen; Moraleda-Barreno, Enrique (Frontiers in Psychiatry, 2020)
Background: Various authors have described the element of impulsive approach, and, also, that of inhibitory control in drug users. These two components have been studied in terms of personality traits, performance on tasks that measure impulsive behavior, and neurophysiology. However, few studies have analyzed the relationship between these constructs. Thus, the aim of the present study is to analyze the relationships between personality traits and performance on impulsivity tasks. Methods: Follow-up study with a baseline assessment at the beginning and end of treatment. The sample was composed of 121 patients undergoing treatment in therapeutic communities. Personality domains were evaluated through the PID-5. The impulsivity tasks employed were the Iowa Gambling Task (IGT), Delay Discounting Test (DDT), Go/No-Go and Stroop test. Results: A relationship was found between DDT scores and the domains of detachment (r = -.315; p<.01), antagonism (r = -.294; p<.01), and disinhibition (r = .215; p<.05). Performance on the Stroop task was significantly associated with psychoticism (r = .232; p<.05) and negative affect (r = .212; p<.05). Multivariate analysis revealed that IGT scores and negative affect predict retention in treatment. Conclusions: These findings partially support the hypothesized relationship between sensation-seeking personality traits and detachment with impulsive choice tasks; and the relationships between negative affect and psychoticism traits with performance on inhibitory control tasks. Further, impulsive choice task scores and negative affect are both shown to predict retention in treatment.